CS07 | Endothelial dysfunction and impaired angiogenesis in Hermansky-Pudlak syndrome (HPS) type 1: studies with endothelial colony forming cells (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Hermansky-Pudlak syndrome (HPS) is an inherited multisystemic disorder caused by a defect of lysosome-related organelles (LRO), like delta granules in platelets, melanosomes in melanocytes and Weibel Palade Bodies (WPB) in endothelial cells (EC). HPS is characterized by oculocutaneous albinism with nystagmus, bleeding diathesis and, in some cases, extra-hematological complications such as pulmonary fibrosis, granulomatous colitis and immunodeficiency. Eleven genes have been identified as causative for HPS in humans. The most severe subtype of HPS is HPS-1, in which variants affect the HPS1 protein. The mechanisms involved in the pathogenesis of HPS have already been investigated in melanosomes, alveolar epithelial cells and platelet delta granules but little is known about EC function in HPS, except for one study showing impaired maturation of WPB in endothelial colony forming cells (ECFC) isolated from an HPS-2 patient. Our aim was to investigate endothelial function, WPB secretion and angiogenesis of ECFC isolated from an HPS-1 patient.